TINJAUAN FALSAFAH PRAGMATISME DARI ASPEK PEMIKIRAN POLITIK PERBANDINGAN - Syed Ismail, Sharifah Hayaati (Jurnal Syariah, 2019)
Political thought has been the most active area of Muslim and Western intellectual life. Many theories and ideologies had been introduced through scientific and traditional approaches especially by the Western to politicize and develop peoples’ mind. The ideas and ideologies differ from time to time based on needs and changes in human activities. One of the ideas introduced by the Western people is known as pragmatism. This article describes the philosophical background of the idea and compares it with the practical views of siyasah shar’iyyah. The writer’s main intention is to show the continuity as well as the comprehensiveness of the Islamic political thought eventhough many of the theories are not labelled in modern political terms.